2020
DOI: 10.5194/amt-13-645-2020
|View full text |Cite
|
Sign up to set email alerts
|

Using ground radar overlaps to verify the retrieval of calibration bias estimates from spaceborne platforms

Abstract: Abstract. Many institutions struggle to tap into the potential of their large archives of radar reflectivity: these data are often affected by miscalibration, yet the bias is typically unknown and temporally volatile. Still, relative calibration techniques can be used to correct the measurements a posteriori. For that purpose, the usage of spaceborne reflectivity observations from the Tropical Rainfall Measuring Mission (TRMM) and Global Precipitation Measurement (GPM) platforms has become increasingly popular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Calibrating ground‐based radars using space‐borne radar data have seen ongoing investigation and application over the last decade (Crisologo & Heistermann, 2019; Schwaller & Morris, 2011; Warren et al, 2018, 2020) and are now used operationally in Australia and implemented in open source radar software (https://docs.wradlib.org/en/stable/). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Calibrating ground‐based radars using space‐borne radar data have seen ongoing investigation and application over the last decade (Crisologo & Heistermann, 2019; Schwaller & Morris, 2011; Warren et al, 2018, 2020) and are now used operationally in Australia and implemented in open source radar software (https://docs.wradlib.org/en/stable/). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the method of Cao et al. (2013) adopted in previous works (Crisologo & Heistermann, 2020; Warren et al., 2018), this new method makes use of local PSD retrievals based on the DPR.…”
Section: Methodsmentioning
confidence: 99%
“…(2018) found that the variation in reflectivity bias over time can reach around 5 dB for radars near Sydney, Australia. Crisologo and Heistermann (2020) also identified low biases of about 5 and 14 dB for two radars in Philippines.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations